The aromaticity of verdazyl radicals and their closed-shell charged species; New Journal of Chemistry; Vol. 42, iss. 24 - Valiev R. R. Rashid Rinatovich; Drozdova A. K. Anna; Petunin P. V. Pavel Vasilievich; Postnikov P. S. Pavel Sergeevich; Trusova M. E. Marina Evgenievna; Cherepanov V. N. Viktor Nikolaevich; Sundholm D. Dage (2018, 2018)
Title screen